2019
DOI: 10.1155/2019/3705264
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Helicobacter pylori Infection and Glycated Hemoglobin A in Diabetes: A Meta-Analysis

Abstract: Background.The association between Helicobacter pylori infection and glycated hemoglobin A has been confirmed in many studies, but these conclusions are still contradictory and controversial. Therefore, we conducted a meta-analysis to resolve the problem of inconsistent results in diabetes.Methods. A comprehensive search was conducted on related researches published in PubMed, Embase, and China Academic Journal Full-text Database (CNKI) from the inception of each database to April 2019. Fixed or random effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
1
22
0
2
Order By: Relevance
“…We found evidence of a graded association between A1C and risk of COVID-19 in a large community-dwelling cohort. The accumulation of differentiated cytotoxic T cells have been linked to impaired glucose homeostasis in pre-clinical work [ 7 ], and associations between A1C and other types of infections have also been observed [ 8 , 9 ]. In several large primary care cohorts a range of infections were more frequent in people with diabetes with worse glycaemic control [ 10 , 11 ], which is consistent with our data.…”
Section: Discussionmentioning
confidence: 99%
“…We found evidence of a graded association between A1C and risk of COVID-19 in a large community-dwelling cohort. The accumulation of differentiated cytotoxic T cells have been linked to impaired glucose homeostasis in pre-clinical work [ 7 ], and associations between A1C and other types of infections have also been observed [ 8 , 9 ]. In several large primary care cohorts a range of infections were more frequent in people with diabetes with worse glycaemic control [ 10 , 11 ], which is consistent with our data.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled OR was 1.27 (95% CI, 1.11‐1.45; P = .0001), significant only among patients with type 2 DM (OR, 1.43; 95% CI, 1.11‐1.85) and more evident in Asians 8 . In agreement, a meta‐analysis including 35 studies with 4401 diabetic patients, showed that glycated haemoglobin A (HbA) levels were significantly higher in patients with H pylori infection compared to uninfected subjects (weighted mean difference = 0.50; 95% CI, 0.28‐0.72; P < .001), without any difference related to the type of DM or study design 9 …”
Section: Metabolic Disordersmentioning
confidence: 69%
“…8 In agreement, a meta-analysis including 35 studies with 4401 diabetic patients, showed that glycated haemoglobin A (HbA) levels were significantly higher in patients with H pylori infection compared to uninfected subjects (weighted mean difference = 0.50; 95% CI, 0.28-0.72; P < .001), without any difference related to the type of DM or study design. 9 In Saudi Arabia, a study included 212 type 2 DM patients aged ≥ 40 years and 209 age-matched non-diabetic subjects. H pylori prevalence was significantly higher in overweight and obese non-diabetic subjects (P = .013).…”
Section: Diabetesmentioning
confidence: 99%
“…Besides that, the H. pylori infection not only increase the risk of DM, but it also impairs the satisfactory control of glycemic levels in DM patients. A meta-analysis that included 35 studies observed that the glycated hemoglobin A levels were significantly higher in H. pylori -positive patients when compared to H. pylori negative individuals (weighted mean difference 0.50, 95%CI: 0.28-0.72, P < 0.001)[ 135 ]. However, the fact that these studies do not take into account other factors that influence the glycemic control, such as obesity index and smoking status, constitute an important limitation[ 134 , 135 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%
“…A meta-analysis that included 35 studies observed that the glycated hemoglobin A levels were significantly higher in H. pylori -positive patients when compared to H. pylori negative individuals (weighted mean difference 0.50, 95%CI: 0.28-0.72, P < 0.001)[ 135 ]. However, the fact that these studies do not take into account other factors that influence the glycemic control, such as obesity index and smoking status, constitute an important limitation[ 134 , 135 ]. Among the hypothesis on how does H. pylori increases the risk of DM, it is believed that the increased cytokine production leads to the phosphorylation of serine residues from the insulin receptor substrate, whose linkage with insulin receptors turns deficient[ 136 ].…”
Section: Extragastric Manifestationsmentioning
confidence: 99%